Pengaruh Work Stress terhadap Work-Life Balance pada Developer di Sagara Technology - Elsa Nurulita; Suhana (Bandung Conference Series: Psychology Science, 2022)
Abstract. Work-life balance is a topic that is currently being researched due to changes in the industry [1]. Job stress is an individual's feeling that deviates from its normal function as a result of obstacles and opportunities in the workplace [2]. This study aims to determine how much influence work stress has on the work-life balance of developers at Sagara Technology. Quantitative research method is used in this research. Research subjects are 42 developers at Sagara Technology. The measuring instruments used are the Work-Life Balance Scale developed by Fisher et al [3] and the Job Stress Scale developed by Parker & Decotiis [2]. Multiple linear regression is used as data analysis in this research. The results showed that 69.05% of developers at Sagara Technology have a low level of work stress and 73.81% of developers have a high level of work-life balance. This study also shows that simultaneously the aspects of work stress have an effect of 64% on work-life balance. Partially time stress aspect has an effect of 50.8% and the anxiety aspect has an effect of 13.2%. Abstrak. Work-life balance merupakan topik yang sedang marak diteliti karena perubahan-perubahan yang terjadi di industri [1]. Work stress merupakan perasaan individu yang menyimpang dari fungsi normalnya sebagai akibat dari hambatan dan peluang dalam pekerjaan yang dilakukan [2]. Penelitian ini bertujuan untuk mengetahui seberapa besar pengaruh work stress terhadap work-life balance pada developer di Sagara Technology. Metode penelitian kuantitatif dipakai sebagai metode penelitian. Subjek penelitian adalah developer di Sagara Technology sebanyak 42 responden. Alat ukur yang dipakai dalah Work-Life Balance Scale yang dikembangkan oleh Fisher et al [3] dan Job Stress Scale yang dikembangkan oleh Parker & Decotiis [2]. Multiple linear regression merupakan analisis data yang dipakai dalam penelitian ini. Hasil penelitian menunjukkan sebanyak 69.05% developer di Sagara Technology memiliki tingkat work stress yang rendah dan sebesar 73.81% developer di Sagara Technology memiliki tingkat work-life balance yang tinggi. Penelitian ini pun menunjukkan bahwa secara simultan, aspek dari work stress memberikan pengaruh sebesar 64% terhadap work-life balance. Secara parsial, aspek time stress memberikan pengaruh sebesar 50.8% dan aspek anxiety memberikan pengaruh sebesar 13.2%.